Liminalitas pada Pertunjukan Ronggiang : Suatu Bentuk Kesenian Tari Tradisi Masyarakat di Kabupaten Pasaman Barat - Celsi Novia Biwis; Nurmalena Nurmalena; Hardi Hardi; Muhammad Fikri (INDO PUBLISHING, 2026)
This study aims to analyze the forms of liminality that occur in Ronggiang dance performers. This study uses a qualitative method in the Liminality approach. Data were obtained through observation, interviews, documentation, and literature studies. The research sources consisted of Ronggiang singers, first dancers, and children of Ronggiang singers. Data were collected through the stages of data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that the initiation process in Ronggiang performances consists of a separation stage, a transition stage (Liminal), and a re-acceptance stage in the social structure. In the liminal phase, Ronggiang performers experience changes in social identity through processes, behavioral adjustments, and involvement in the rules and symbols of the performance. This phase creates an ambiguous condition where individuals are between old and new identities as part of the Ronggiang community. In addition, liminality in Ronggiang performances also shows the formation of social solidarity and relationships between performers.